Students’ learning style preferences and the impact on their achievements in mainstream English 1 (bel 200): a study on UiTM students in the northern region (branch campuses of UiTM in Perlis, Penang and Kedah) / Francis Xavier A.S.Rajoo and Mak Kem Seng - A.S.Rajoo, Francis Xavier; Mak, Kem Seng (Research Management Institute, 2003)
In the learning process, various methods and ways are being utilised by learners. Learners engage different behaviour and styles that may assist in effective learning. Numerous studies of learning styles conducted by Reid (1993, 1995) have shown that successful learning can take place if competent teachers and educators know how to make the students utilise their correct learning style preferences. Teachers and educators equipped with the knowledge of the rudiments of various learning style preferences would have an added advantage when delivering their lessons. The background knowledge of the learning style preferences will enable the teachers and educators to empower their students to acquire a second language and simultaneously pave the way for their learners to become autonomous learners. Teachers and educators can provide assistance by identifying the strengths and weaknesses in their students’ learning style preferences. At the same time, they can also facilitate the appropriate implementation of teaching methods catering to the various learning style preferences of their students. Research has shown that teachers and educators who cater for the students’ different learning style preferences in their teaching methodologies can assist their learners to maximise second language acquisition. Furthermore, research findings have also substantiated the basis that greater satisfaction and achievements were reported amongst students whose learning styles matched with those appropriate teaching methodologies (Wesche, 1981). It is hoped that this limited study could provide useful insights as well as pave the way for better achievements and performances by the students. Findings in this study have shown that students yearn for the correct methodology tailoring for their learning style preferences. The insights gained could also prove useful for teachers and educators in empowering their students to become autonomous learners in the acquisition of English as a second language.